Hypophysitis, Panhypopituitarism, and Hypothalamitis in a Scottish Terrier Dog. (26th July 2017) - Polledo, L.; Oliveira, M.; Adamany, J.; Graham, P.; Baiker, K.
Abstract : A 6‐year old male neutered Scottish Terrier was referred with a 1 week history of progressive lethargy and anorexia. Neurological examination localized a lesion to the forebrain and hormonal testing showed panhypopituitarism. Magnetic resonance imaging (MRI) of the brain revealed a rounded, well‐defined, suprasellar central mass. The mass was slightly hyperintense to the cortical grey matter on T2‐weighted (T2W), hypointense on T1‐weighted (T1W) images and without T2* signal void. There was a central fusiform enhancement of the mass after contrast administration which raised the suspicion of a pituitary neoplasm. Rapid deterioration of the dog prevented further clinical investigations. Histopathologic examination revealed a lymphocytic panhypophysitis of unknown origin suspected autoimmune involving the hypothalamus (hypothalamitis). This is a unique case report of a dog presenting with inflammatory hypophysitis and hypothalamitis of suspected autoimmune origin with detailed clinical, MRI, histology and immunohistochemistry findings.